THE EFFECT OF BRAND PROMINENCE AND MUSIC INVOLVEMENT ON BRAND RECALL IN MUSIC VIDEO - Wijaya, Irenia Binardi; Cokki, Cokki (International Journal of Application on Economics and Business, 2023)
Research in developing countries is still limited, especially regarding product placement in Korean music. This study aims to determine the effect of brand prominence and music involvement on brand recall. This study used the pre-test and post-test experimental method. The Korean music video, namely "It G Ma", was presented to 55 students. The results showed that participants tended to have a stronger brand recall on prominent product placements when they had known the brand before, and music involvement does not affect brand recall.